HDL Particle Size and Functionality Comparison between Patients with and without Confirmed Acute Myocardial Infarction - Raissa de Miranda Teixeira; Nicole Cruz de Sá; Ana Paula Caires dos Santos; Vanessa Rocha Anjos e Silva; Elaine Christine de Magalhães Cabral Albuquerque; Luiz Claudio Lemos Correia; Ricardo David Couto (Cardiology Research and Practice)
Introduction. Cardiovascular diseases (CVDs) continue to be the most common cause of death worldwide, and acute myocardial infarction (AMI) is noteworthy due to its great magnitude. Objectives. This study was carried out to evaluate the structure (molecular and particle size) and functionality of high-density lipoprotein (HDL) shortly after AMI, in the presence of acute inflammatory response. Casuistic and Methods. A cross-sectional, observational study was conducted between January 2015 and August 2016, with a total convenient sample of 85 patients. The patients’ data were segregated according to the Registry of Acute Myocardial Infarction (REAMI), with 45 confirmed AMI patients. The study groups consisted of patients from both sexes, older than 35 years, presented to the Hospital São Rafael (HSR) initially with AMI clinical symptoms. In addition, 40 nonischemic control patients (CPs), without AMI symptomatology, and according to previous inclusion criteria, were selected for convenience in an outpatient care unit. The HDL particle size was measured by laser light scattering (LLS), after separation of HDL from apoB-rich lipoproteins. The paraoxonase-1 (PON-1) activity was determined in a spectrophotometer by using paraoxon as a substrate. The other laboratory marker information, secondary data, was obtained in the laboratory system. Results. The HDL particle size, free cholesterol, and hs-CRP analysis showed significant differences when compared between REAMI and CP groups (p<0.0001, p=0.007, and p<0.0001; two-tailed unpaired t-test, respectively). Regarding paraoxonase, the data comparison between REAMI and CP groups was also significantly different (p<0.0067; two-tailed unpaired t-test). Conclusion. Despite an important current database on the HDL cholesterol role, our study provides relevant complementary information about the HDL particle susceptibility to the inflammation following AMI. The HDL particles’ quantitative and functional attributes should be measured as markers of HDL functionality.